Nutrient elements in grassland : soil-plant-animal relationships - Whitehead, D. C. (David Charles) (Cabi Ser., 2000)
This book deals with the concentrations and transformations of nutrient elements in soils, grassland plants and ruminants, particularly sheep and cattle. Data are restricted to those relevant to temperate grasslands. After an introductory chapter, the next 3 chapters deal with nutrient elements in soils, the uptake and concentration of nutrients in herbage, and nutrient elements in ruminant animals. The rest of the book deals with individual nutrients: nitrogen, phosphorus, sulfur, major cations (K, Na, Ca and Mg), trace element cations (Fe, Mn, Zn, Cu and Co), halogens (Cl and I), and other trace elements (B, Mo and Se). For each element, attention is given to its forms and availability in soils, uptake and distribution in grassland plants, role in animal nutrition, and amounts and forms excreted by grazing animals. Influence of management and environmental factors on nutrient concentrations in herbage, and concentrations needed by ruminants, are considered, and nutrient budgets for each element are estimated for intensively and extensively managed grassland.